Tributyl(1-((dimethylamino)(dimethyliminio)methyl)-1,4-dihydropyridin-4-yl)phosphonium Ditrifluoromethanesulfonate - Yiwei Gong; Jas S. Ward; Kari Rissanen; Florian F. Mulks (Molbank, 2023)
Site-selective functionalization of pyridines is a crucial tool for the synthesis of diverse pharmaceuticals and materials. We introduced diiminium pyridine adducts as highly convenient and potent Lewis acids. We report that tributylphosphine selectively adds to the 4-position of pyridine in tetramethyldiiminium pyridine ditrifluoromethanesulfonate, resulting in the formation of the title compound. This finding represents an advancement towards the utilization of diiminium units as organic reagents or catalysts for pyridine functionalization. We also employ computational models to determine fluoride and hydride ion affinities, Fukui function f+(r), molecular electrostatic potential, and pKa values, providing valuable insights for future investigations in this area.